Conformation of dehydropentapeptides containing four achiral amino acid residues – controlling the role of L-valine - Jewgiński, Michał; Krzciuk-Gula, Joanna; Makowski, Maciej; Latajka, Rafał; Kafarski, Paweł (Beilstein Journal of Organic Chemistry, 2014)
Structural studies of pentapeptides containing an achiral block, built from two dehydroamino acid residues (ΔZPhe and ΔAla) and two glycines, as well as one chiral L-Val residue were performed using NMR spectroscopy. The key role of the L-Val residue in the generation of the secondary structure of peptides is discussed. The obtained results suggest that the strongest influence on the conformation of peptides arises from a valine residue inserted at the C-terminal position. The most ordered conformation was found for peptide Boc-Gly-ΔAla-Gly-ΔZPhe-Val-OMe (3), which adopts a right-handed helical conformation.
Keywords: conformation; dehydroalanine; dehydropeptide; dehydrophenylalanine; NMR